(untitled) (De Legibus - Law Journal, 2024)
The evolutionary process of islamic terrorism has been witnessed internationally over the past few decades. The common denominator of the terrorist actions perpetrated by independent cells, groups, and terrorist organizations, which aim is to spread terror and to restrict human freedom, corresponds to the extensive array of dispositional and extrinsic variables that can be interpreted by social sciences, namely Psychology. Although this phenomenon represents a relatively recent threat in the European continent, there arises a need to pay increasing attention to the variables and dynamics that lead to the processes of radicalization and recruitment, which are now focusing on younger populations and being activated within their own countries, where several attacks end up taking place. Considering the fact that terrorism poses a serious threat to transnational security, and given the return of terrorists to their nations, the Psychology of Terrorism accentuates its importance, providing the basis for the development of effective counterterrorism measures by looking at the conduct, identity and motivation of those who are considered to be both martyrs and enemies: the terrorists.